دراسة مقارنة لخاصية مقاومة الاهتراء للراتنج المركب الترميمي المباشر الخلفي الهجين والراتنج المركب ذي الحبيبات الخزفية - جلول, دارين (Latakia University Journal -Medical Sciences Series, 2016)
المقدمة : إن المطلب الجمالي لترميمات الأسنان الخلفية تزايد بشكل الملحوظ في السنوات الأخيرة, لقد طورت العديد من المواد الترميمية السنية لتلبية النواحي الجمالية, الالصاق والخواص الميكانيكية .الهدفَ من هذه الدراسة: تحرّي تأثيرِ إضافةِ المالئاتِ الخزفيّةِ في بعضِ الخصائِص الميكانيكيةِ (مقاومة الاهتراء) لترميماتِ الراتنجِ المركّب المقوّى بالجزيئاتِ المالئةِ الخزفية, وذلك بهدفِ مقارنتِها مع ترميماتِ الراتنج المركّب الهجين الخلفي .مواد وطرائق البحث: تمّ استخدامُ مجموعتين من الراتنج المركّب الهجين الخلفي و هما :-Spectrom - Tetric Ceramو مجموعتين من الراتنج المركّب المقوّى بالجزيئات الخزفية و هما Tetric Evo Ceram - - Ceram-x تألّفت الدراسةُ المخبرية من ستين عيّنةً لدراسةِ اختبارِ مقاومة الاهتراء حيث تم تحضير العينات على شكل اسطوانات بأبعاد (قطر 3ملم ارتفاع 3ملم) .النتائج: أظهر الراتنج المركب Tetric Evo Ceram مقدار اهتراء اقل من باقي الراتنجات الخاضعة للدراسة.الاستنتاجات:لم تظهر فروق دالة احصائياً بين نسب مقاومة الاهتراء لكل من الراتنج المركب الهجين والراتنج المركب المقوى بالجزيئات الخزفية .Introduction :The demand for posterior aesthetic restorations has dramatically increased in recent years. Several new materials have been developed with improved aesthetic, adhesive and mechanical properties.Theoretically, nano-structured dental resin omposites are purported to have increased wear and hardness resistance compared with hybrid composites and may favor the achievement of restoratives with better long-term performance.Aim: The wear resistance of different types of resin composites were evaluated in the in vitro study.Material and methods :Two nanohybrid restorative composites -Tetric®EvoCeram (Ivoclar-Vivadent) and CeramXTM(Dentsply) - were compared with a microhybrid material - Tetric®Ceram (Ivoclar-Vivadent) and hybrid material Spectrom (Dentsply) .wear resistance : fifteen specimens (3x3 mm) of each material were subjected to wear tests .The data were analyzed by 1-way ANOVA(<=0.5).Results :The Tetric®EvoCeram composite resin exhibited significantly less wear than the CeramX and Tetric®Ceram material .Conclusions :In terms of wear resistance, nano-structured composites may perform either similarly or comparativelybetter than a microfilled and hyprid composite .nanohybrid restorative composites can thus be considered as a good restorative material.